Thermal behavior of potassium bromostannate - Galloni, E. E.; Rodriguez de Benyacar, M. A.; Jimenéz de Abedelo, M. E. (AKADEMISCHE VERLAGSGESELLSCHAFT, 1962)
Fil: Galloni, E. E. Comisión Nacional de Energía Atómica; Argentina